Congenital Syphilis After Treatment of Maternal Syphilis With a Penicillin Regimen Exceeding CDC Guidelines - Craig S. Conover; Charles A. Rend; Grayson B. Miller; George P. Schmid (Hindawi Limited, 1998)
Background: Although congenital syphilis usually occurs as a result of a failure to detect and treat syphilis in pregnant women, failures of the currently recommended regimen to prevent congenital syphilis have been reported.